The relationship between athletes' perceptions of Covid-19 and communication with the psychological skills - Sugihartono, Tono; Nopiyanto, Yahya Eko; Raibowo, Septian; Ilahi, Bogy Restu (UIR Press, 2021)
Many athletes experienced psychological problems and communication with their coaches during the Covid-19 pandemic. The purposes of this study was to determine: athletes’ perceptions of Covid-19, communication athletes to coaches, the psychological skills of athletes, the relationship between athletes’ perceptions of Covid-19, and communication athletes-coaches with the psychological skills of Bengkulu athletes during Covid-19. The method used in this research was quantitative with a correlation approach. The population in this research was all Bengkulu athletes who would participate in National Sports Week (PON) Papua 2021, totaling 83 athletes. Sampling technique used is total sampling so that all populations were used as research samples. Research techniques and instruments used individual perception about Covid-19 questionnaire, the coaches-athletes relationship questionnaire, and the psychological skills inventory for sports questionnaire. Data analysis technique used multiple regression with SPSS at the significance level of 0.05. The result of this study indicates that: (1) athletes’ perceptions of Covid-19 have a good perception with score 70.00 – 84.00, (2) communication athletes to coaches have very good communication with score 41.39 - 46.00, (3) the psychological skills of athletes have a good category with score 129.20 - 159.9, (4) there was a significant relationship between athletes’ perceptions of Covid-19, communication athletes-coaches with psychological skills level of Bengkulu athletes during pandemic Covid-19 with sig. score 0.005 < 0.05.